A avaliação da lei complementar n° 233/2005 em relação a exploração sustentável das florestas em Mato Grosso: sua eficácia nas políticas ambientais no Brasil - Alessandra Maria Filippin dos Passos Santos; Aumeri Carlos Bampi; Wylmor Constantino Tives Dalfovo (Confins)
Given the importance of forests and the role of public environmental policies, using an interdisciplinary methodology, this study explained the various levels of effectiveness of Complementary Law No. 233/2005, which aims to ensure the flora and allows sustainable exploitation, implanted in the state of Mato Grosso. Eight municipalities were selected, located in the Amazon biome, with significant indicators of deforestation and illegal logging. The analysis considered the potential in areas of standing forest, from which seven municipalities had areas suitable for legal exploitation, the forest managements implemented, environmental assessments against flora and the discharge of these fines, of which only 4% were paid. . To analyze the behavior of deforestation in relation to the independent variables, a multiple linear regression model was used. The estimation resulted in a positive relationship between management and deforestation, demonstrating the feeling of false legality. Logging establishments did not show a statistical relationship with deforestation, unlike the employment link variable, which was positive. The assessments against flora showed a negative relationship with deforestation, which is attributed to deficits related to the application of sanctions and the payment of fines in the municipalities studied. Thus, it was understood that the complementary law alone is not able to act efficiently in relation to the protection of flora and the promotion of sustainable activities, requiring an alignment between the agents, the State and the competent bodies, evidencing that the factors associated with deforestation in these municipalities are complex and are not related only to the timber sector.